A Descriptive Study to Assess the Knowledge Regarding Effects of Smoking and Prevention among Adults Residing in Selected Urban Area at Kolhapur - Sourabh Shinde; Samruddhi Shinde; Saniya Mujawar; Sumit Sutar; Sanika Kharat; Samruddhi Kondekar; Suhel Mulla; Suhel Pathan; Suraj Salve; Dr. Praveen Subravgoudar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and Objectives: Smoking is a leading cause of preventable diseases and premature death globally, with the World Health Organization (WHO) reporting over 8 million deaths annually, including 7 million from direct tobacco use and 1.2 million from second-hand smoke exposure. In India, approximately 28% of adults use tobacco, contributing to a significant health burden. This study assesses the knowledge regarding the effects of smoking and prevention strategies among adults in a selected urban area of Kolhapur. Objectives: 1) Assess the level of knowledge regarding the harmful effects of smoking among adults; 2) Identify the association of knowledge scores with selected socio-demographic variables. Methods: A quantitative descriptive survey approach with a non-experimental descriptive research design was employed. Non-probability purposive sampling selected 385 adults aged 18-45 from Kasba Bawada, Kolhapur. Data were collected using a structured questionnaire with demographic variables and 30 knowledge items. Ethical clearance, permissions, and informed consent were obtained. Data analysis included descriptive statistics (frequencies, percentages, mean, standard deviation) and inferential statistics (chi-square tests). Results: Preliminary findings indicate a majority of participants had good knowledge (87.79%), with 8.31% poor and 3.90% average. Significant associations were observed with age, gender, education, and smoking status (p<0.05), while no associations were found with religion, occupation, income, or family smoking history. Interpretation and Conclusion: Adults in the selected urban area of Kolhapur demonstrate a generally good level of knowledge about smoking effects and prevention, though gaps exist in the poor and average knowledge groups. These findings underscore the need for targeted educational interventions to enhance awareness and support public health strategies.